3 - Human Capital Flight: Stratification, Globalization, and the Challenges to Tertiary Education in Africa1 - Benno J. Ndulu, (Journal of Higher Education in Africa, 2004)
Development efforts in Africa are greatly hampered by the flight of both finan- cial capital and by human capital (brain drain). Even those professionals who remain frequently engage in less-skilled occupations because of weak national economies. The historic “push” factors of economic and demographic pres- sures are currently intensified by globalization, movement toward a knowledge-based economy, and global demographic trends. Given that a con- tinuation of fast-paced loss of the region’s talent is likely to continue for some time, the author urges the adoption of strategies to enhance the capacity of African nations for training, retaining skilled manpower, and reversing some brain drain. Tertiary education institutions are evolving to fill the quantity and quality deficiencies in the region, including the emergence of global educa- tion, new global knowledge-sharing mechanisms, information technology, net- working, and parallel systems such as independent certification and knowl- edge intermediaries. The article concludes with several recommendations for squarely addressing the underlying push factors toward emigration.